2021
DOI: 10.1001/jamanetworkopen.2021.18702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Targeted Behavioral Science Messages on COVID-19 Vaccination Registration Among Employees of a Large Health System

Abstract: Dr Santos had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis. Drs Chabris and Meyer contributed equally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 7 publications
0
52
2
Order By: Relevance
“…A field experiment (pre-print) found that a booking reminder emphasising vaccine effectiveness was more effective than one emphasising social benefits and others having had the vaccine [ 17 ]. Another field RCT found that an email comparing the risks of the COVID-19 vaccine to the more severe risks of the virus increased uptake [ 23 ]. However, this intervention had a similar impact on uptake as an email focusing on social norms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A field experiment (pre-print) found that a booking reminder emphasising vaccine effectiveness was more effective than one emphasising social benefits and others having had the vaccine [ 17 ]. Another field RCT found that an email comparing the risks of the COVID-19 vaccine to the more severe risks of the virus increased uptake [ 23 ]. However, this intervention had a similar impact on uptake as an email focusing on social norms.…”
Section: Resultsmentioning
confidence: 99%
“…A field experiment (pre-print) found that a booking reminder emphasising to ‘join the 3.5 million vaccinated citizens’ increased vaccine uptake, but to a lesser extent than one emphasising the personal benefit of getting vaccinated [ 17 ]. Another field RCT with unvaccinated health care workers found that sending an email telling them that more than 11 million Americans, including many of their colleagues, had been vaccinated increased uptake [ 23 ]. However, this effect was similar to the effect of an email comparing the risks of the vaccine to the more severe risks of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Hispanics unvaccinated for COVID-19 are non-homogenous and exist on a continuum that includes those that are hesitant (e.g., "wait and see") or facing logistical barriers (e.g., time off work, transportation) to those that whose views are entrenched and may require substantial education, or employment requirements, to change their behavior. There are broad tools like mandates to get vaccinated as a requirement for employment, education, or travel and more subtle nudges employed by behavioral economists [28][29][30]. While recognizing that the relationship between attitudes and behaviors is complex [31], utilization of positive, targeted [32], and culturally responsive messaging on COVID-19 vaccines and using vaccinated Hispanic health-care workers as vaccine ambassadors targeting the themes identified here should be evaluated in controlled research.…”
Section: Discussionmentioning
confidence: 99%
“…time off work, transportation) to those that whose views are entrenched and may require substantial education, or employment requirements, to change their behavior. There are broad tools like mandates to get vaccinated as a requirement for employment, education, or travel, and more subtle nudges employed by behavioral economists [28][29][30] . While recognizing that the relationship between attitudes and behaviors is complex, 31 utilization of positive, targeted 32 , and culturally responsive messaging on COVID-19 vaccines and using vaccinated Hispanic health-care workers as vaccine ambassadors targeting the themes identified here should be evaluated in controlled research.…”
Section: Discussionmentioning
confidence: 99%